2004
DOI: 10.1111/j.1600-0404.2004.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of levetiracetam in pharmacoresistant continuous spikes and waves during slow sleep

Abstract: Even if our report is anecdotal, LEV expands the spectrum of antiepileptic drugs that can be used for the treatment of CSWS. LEV efficacy should be confirmed in larger series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 14 publications
4
36
0
Order By: Relevance
“…Two other patients without improvement of the EEG had neuropsychological improvement (Aeby et al 2005). Benefit was also reported in another small series (Capovilla et al 2004). There was 1 case report of improvement in a child with the related Laudau-Kleffner syndrome (Kossoff et al 2003).…”
Section: Levetiracetamsupporting
confidence: 57%
“…Two other patients without improvement of the EEG had neuropsychological improvement (Aeby et al 2005). Benefit was also reported in another small series (Capovilla et al 2004). There was 1 case report of improvement in a child with the related Laudau-Kleffner syndrome (Kossoff et al 2003).…”
Section: Levetiracetamsupporting
confidence: 57%
“…Recently, reports have suggested that LEV may be useful in CSWS. [1011] Capovilla et al . [10] reported total seizure control in two of three patients with CSWS.…”
Section: Discussionmentioning
confidence: 99%
“…[1011] Capovilla et al . [10] reported total seizure control in two of three patients with CSWS. Lennox-Gastaut syndrome is an epileptic encephalopathy characterized by multiple seizure types, mental retardation, and a slow spike-and-wave pattern on electroencephalography.…”
Section: Discussionmentioning
confidence: 99%
“…Resolution of ESES had been achieved with conventional antiepileptic drugs (AEDs) including ethosuximide [28,29], valproic acid [25,30], benzodiazepines [22,[30][31][32], levetiracetam [17,33,34], and sulthiame [17,22]. When these agents fail to normalize the EEG, a trial with second-line agents such as steroids [17,[25][26][27] or high-dose diazepam [35,36] is attempted.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%